IMPLEMENTASI TOTAL QUALITY MANAJEMEN (TQM) DALAM PENGELOLAAN MADRASAH ALIYAH AL MAWADDAH WARRAHMA KOLAKA - novita, novita; tanaka, ahmad; b, syamsuddin (Jurnal Teknologi Pendidikan Madrasah, 2020)
The application of TQM in the field of education, in the management of institutions to improve quality must be carried out in an integrated and sustainable manner, so that education as a service can meet customer needs both today and in the future with the TQM approach, it is hoped that education will be able to produce quality graduates and can improve. quality on an ongoing basis. Based on this, this study aims to explain about the implementation of total quality management in the management of Madrasah Aliyah Al Mawaddah Warrahma Kolaka. This study uses a qualitative approach, with observation data collection techniques, interviews and documentation. As for analyzing the data using descriptive qualitative data analysis. In this study, researchers used three triangulations, namely triangulation of sources, methods and investigators. Source triangulation is used by comparing the results of observation data, interviews and documentation. Method triangulation is done by collecting circulating data such as observation, interviews and documentation. Investigator triangulation bends the data obtained by an informant with other informants. This study concludes that: The implementation of Total Quality Management in the management of MA Al Mawaddah Warrahmah Kolaka by looking at 2 variables, namely the standard management and management variables based on madrasah in an effective school context, most of them have been implemented. This can be seen in the Planing Do, Check, Action carried out by MA Al Mawaddah Warrahmah Kolaka although there are still things that have not been completely fulfilled from the aspects of assessment such as the Ratification of the Decree at the Ministry of Religion Distik / Kan and so on.